Complete sequence of multidrug resistance p9134 plasmid and its variants including natural recombinant with the virulence plasmid of Salmonella serovar Typhimurium - Kubasova, Tereza; Matiasovicova, Jitka; Rychlik, Ivan; Juricova, Helena (Plasmid, 2014)
In this study we determined the complete nucleotide sequence of multidrug-resistance plasmid p9134, and its variants p9134dT and p9134dAT which spontaneously lost either tetracycline or both tetracycline and ampicillin resistance, respectively. The plasmids were 133,802 bp, 109,512 bp and 127,291 bp in size, respectively, and their basic backbone was similar to that of IncI plasmids. Genes coding for ampicillin (blaTEM), chloramphenicol (catA1), streptomycin (strA, strB), tetracycline (tetA(A)) and gentamicin (aac(3)-IV) resistance were confirmed in wild-type p9134. Moreover, a gene for hygromycine resistance (hph) and a putative gene for apramycin resistance were newly determined. In p9134dAT, a continuous sequence coding for ampicillin and tetracycline resistances was lost. Genetic rearrangements in p9134dT were more complex and 2 recombination events must have occurred. During the first one, the tetracycline resistance locus was replaced with rck, srgB, srgA, orf7 and pefI originating from Salmonella virulence plasmid pSLT. During the second one, ydjA, pifA and repC genes from p9134 were replaced with repA2, PSLT025 and PSLT026 genes from pSLT. Our findings indicate that recombination event between unrelated plasmids might be quite common and may lead to the generation and selection of plasmids both transferring antibiotic resistance and increasing virulence of their host.
Keywords: rekombinace genetická; Salmonella; Antibiotic resistance; Plasmid sequence; sekvenční analýza DNA; rezistence na tetracyklin; Conjugation; Tetracycline Resistance; Plasmids; Recombination; plazmidy; mnohočetná bakteriální léková rezistence; Recombination, Genetic; Salmonella typhimurium; Sequence Analysis, DNA; Drug Resistance, Multiple, Bacterial